Singularity avoidance controller design for spacecraft attitude control using double-gimbal variable-speed control moment gyro - Barman, Saumitra; Sinha, Manoranjan (European journal of control, 2023)
A sub-optimal singularity avoidance large angle rest-to-rest attitude maneuver control of a rigid spacecraft actuated using a double-gimbal variable-speed control moment gyro (DGVSCMG) is proposed for avoiding the control torque saturation and the gimbal lock singularity. To achieve this objective, a modified model predictive static programming (MPSP) algorithm subject to control and state constraints is proposed and developed. A cuboid rigid spacecraft equipped with a single DGVSCMG device for the attitude control is considered to validate the proposed control algorithm. A new MPSP based control architecture for the attitude control of a spacecraft using a DGVSCMG is developed, wherein the desired gimbal angle rates and rotor spin acceleration are taken as the control input and computed directly using the MPSP algorithm without requiring the steering law. The control law ensures attitude stabilization of the spacecraft-DGVSCMG system while successfully avoiding the control input saturation and the gimbal lock singularity of the DGVSCMG, thereby enabling large angle attitude maneuvers. Multiple test cases of rest-to-rest attitude maneuvers are simulated to show the efficacy of the proposed control.